2020
DOI: 10.21448/ijsm.594839
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Secondary Metabolites in Two Cousinia species

Abstract: Cousinia is one of the widespread genera of Asteraceae family. According to previous studies on some Cousinia species it was found that these species are rich of triterpenes, sesquiterpenes, flavonoids, acetylenes and steroids. According to our knowledge, there are no published reports on the chemical composition of C. iconica Hub.-Mor. and C. aintabensis Boiss. & Hausskn., thus we aimed to investigate secondary metabolites of these species. In this study, the phytochemical constituents of these species were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Based on the results, the plant extract showed the highest TPC and TFC values for the microwave-assisted extraction technique [35]. In another study in 2020, Paşayeva et al revealed that the ethyl acetate extract of E. kotschyi showed the highest total phenolic (173.710 ± 1.088 mg gallic acid equivalent/g extract) and total flavonoid contents (86.978 ± 0.650 mg catechin equivalent/g extract), as well as indicating the highest antioxidant activity against the DPPH radical [36].…”
Section: Determination Of the Total Phenolic And Flavonoid Contentsmentioning
confidence: 99%
“…Based on the results, the plant extract showed the highest TPC and TFC values for the microwave-assisted extraction technique [35]. In another study in 2020, Paşayeva et al revealed that the ethyl acetate extract of E. kotschyi showed the highest total phenolic (173.710 ± 1.088 mg gallic acid equivalent/g extract) and total flavonoid contents (86.978 ± 0.650 mg catechin equivalent/g extract), as well as indicating the highest antioxidant activity against the DPPH radical [36].…”
Section: Determination Of the Total Phenolic And Flavonoid Contentsmentioning
confidence: 99%